Sodium ion conductor and sodium ion solid battery

By using alternating current field treatment and synergistic effect of high-priced metal salts and ethyl orthosilicate in the preparation of sodium ion conductors, the problems of low conductivity, high cost and poor safety of sodium ion conductors are solved, and a higher The conductivity and lower production costs while enhancing safety.

CN119419343APending Publication Date: 2025-02-11JIANGSU JIUTAI BATTERY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411560345.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing sodium ion conductors have low conductivity, high preparation cost, and unsafe preparation process. They have not paid attention to the synergistic impact of the prices of different metal sources on the conductivity.

Method used

Sodium ion conductors are prepared by molding the solution-assisted solid phase reaction method, alternating current field treatment instead of high-temperature calcination, combining the synergistic effect of high-priced transition metal salts and ethyl orthosilicate, the molar ratio of sodium salt is adjusted to optimize the conductivity.

Benefits of technology

It improves the conductivity of sodium ion conductors, reduces preparation costs, enhances safety, and achieves higher conductivity at room temperature, which is more parameter controllable and safer than the high-temperature calcination process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117717750000061
    Figure BDA0005117717750000061
  • Figure BDA0005117717750000071
    Figure BDA0005117717750000071
  • Figure BDA0005117717750000072
    Figure BDA0005117717750000072
Patent Text Reader

Abstract

The invention belongs to a new energy technology, and particularly relates to a sodium ion conductor and a sodium ion solid battery, the sodium ion conductor is prepared from a sodium source, a transition metal salt, a heterovalent metal salt, a phosphorus source and tetraethoxysilane through a solution-assisted solid-phase reaction method; wherein the sodium source is selected from sodium halide, sodium bicarbonate or sodium hydroxide, and the sodium halide is selected from any one of sodium chloride or sodium fluoride; the transition metal salt is selected from pentavalent or tetravalent transition metal salt; the heterovalent metal salt is selected from divalent or trivalent heterovalent metal salt; the phosphorus source is selected from phosphoric acid aqueous solution. The sodium ion conductor and the sodium ion solid battery prepared by the invention are high in conductivity and low in preparation cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to new energy technology, and in particular relates to a sodium ion conductor and a sodium ion solid battery. Background Art

[0002] Lithium-ion batteries have been used as mobile power sources for decades due to their high capacity and low mass. However, the raw materials for lithium-ion batteries are too expensive. In recent years, attempts have been made in the energy field to prepare solid conductive materials using sodium ions, which are more abundant and cheaper.

[0003] The sodium-ion batteries currently under research mainly involve two forms: liquid organic electrolytes and solid electrolytes. Liquid organic electrolytes are prone to leakage, combustion, explosion, etc., and their safety cannot be guaranteed. Compared with liquid organic electrolytes, solid electrolytes have improved safety performance, but the improvement of their electrical conductivity is an urgent problem to be solved in the energy field.

[0004] The technical bottlenecks in improving the conductivity of sodium ion solid electrolytes mainly involve:

[0005] The high conductivity of sodium ions requires a high temperature environment. However, the high temperature synthesis process will lead to the formation of impurities, resulting in a decrease in conductivity.

[0006] Since solid electrolytes are prone to produce grain boundaries during the preparation process, dendrites produced during the battery preparation process grow along the grain boundaries, affecting conductivity.

[0007] There are many technologies currently available that focus on improving the conductivity of sodium-ion batteries. All of them involve mixing multiple metal ions with sodium ions to prepare a precursor, and then calcining the precursor at high temperature to obtain a finished solid electrolyte. The focus of this type of technology is on the selection of multiple metal ion sources; however, the high-temperature calcination process itself will lead to the loss of conductive ions, and it is costly, time-consuming, has many uncontrollable parameters, and is prone to safety accidents.

[0008] In the prior art, there is no research focusing on the synergistic effect of the prices of different metal sources on the conductive properties of sodium ion conductors. Summary of the invention

[0009] The purpose of the present invention is to provide a sodium ion conductor and a sodium ion solid battery to solve the problems of low conductivity, high preparation cost, unsafe preparation process, etc. existing in the sodium ion conductor.

[0010] In order to achieve the above object, the present invention provides the following technical solutions:

[0011] A sodium ion conductor is obtained by molding a sodium source, a transition metal salt, an isovalent metal salt, a phosphorus source and tetraethyl orthosilicate through a solution-assisted solid phase reaction method;

[0012] Wherein, the sodium source is selected from sodium halide, sodium bicarbonate or sodium hydroxide, and the sodium halide is selected from any one of sodium chloride or sodium fluoride;

[0013] The transition metal salt is selected from pentavalent or tetravalent transition metal salts;

[0014] The heterovalent metal salt is selected from divalent or trivalent heterovalent metal salts;

[0015] The phosphorus source is selected from aqueous phosphoric acid.

[0016] Wherein, the transition metal in the pentavalent transition metal salt is selected from any one of niobium, tantalum, antimony and arsenic;

[0017] The transition metal in the tetravalent transition metal salt is selected from any one of zirconium, hafnium, cerium and tin;

[0018] The transition metal salt is selected from acetate or nitrate.

[0019] Wherein, the transition metal in the trivalent transition metal salt is selected from any one of iron, aluminum and chromium;

[0020] The transition metal in the divalent transition metal salt is selected from any one of zinc, manganese and nickel;

[0021] The transition metal salt is selected from acetate or nitrate.

[0022] The molar ratio of the sodium source, transition metal salt, isovalent metal salt, phosphorus source and tetraethyl orthosilicate is as follows: (1-2):2:(1.5-2.5):(0.5-1):2.

[0023] The steps of molding a sodium ion conductor from a sodium source, a transition metal salt, an isovalent metal salt, a phosphorus source and tetraethyl orthosilicate by a solution-assisted solid phase reaction method are as follows:

[0024] Step S1: adding a predetermined amount of sodium source, transition metal salt, isovalent metal salt, phosphorus source, and tetraethyl orthosilicate into deionized water at once, and stirring well to obtain a gel solution;

[0025] Step S2: drying the gel solution obtained in step S1, and then subjecting it to heat treatment to obtain a precursor powder;

[0026] Step S3: molding the precursor powder to obtain a green body.

[0027] Wherein, in step S1, the amount of deionized water added is more than 20 times the mass of the sodium source;

[0028] In step S2, the drying temperature is 70-80 degrees Celsius.

[0029] The following steps are also included:

[0030] Step S4: flash-sintering the obtained green body under an alternating current electric field;

[0031] Step S5: maintaining the flash-sintered green body at a preset current density for a certain period of time, then removing the AC electric field and cooling the green body to room temperature to obtain a solid electrolyte sodium ion conductor.

[0032] Wherein, in the step S4, the electric field strength of the AC electric field during flash burning is 60-100 V / cm;

[0033] In step S5, the holding time after flash burning is 1-10 minutes, and the preset current density is 50-70 mA / mm 2 .

[0034] The present invention further provides a sodium ion solid battery, comprising a positive electrode active material layer, a negative electrode active material layer and a solid electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, wherein the solid electrolyte layer contains any of the sodium ion conductors described above.

[0035] The mass ratio of the sodium ion conductor to the solid electrolyte layer is 20-40%.

[0036] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0037] 1. Replace high temperature calcination with AC electric field treatment to avoid the loss of effective conductive ion components and three-dimensional space structure.

[0038] In view of the performance bottleneck of the existing technology, the present invention speculates that the high-temperature calcination process will affect the effective ion composition or structure in the electrolyte. For example, high-temperature calcination will destroy the effective three-dimensional spatial structure such as sodium ions, phosphorus ions or silicon-oxygen bonds. Therefore, the inventors try to replace the high-temperature calcination process with other means to treat the precursor molded into a green body. Since the conductive ions will produce directional movement under the action of the electric field, the inventors try to treat the green body obtained after the precursor powder is pressed with an alternating electric field. After adjusting the electric field strength, the appropriate electric field strength range is found. The green body obtained by pressing is treated within this range, which can obtain a more suitable sample density and a better microstructure than the high-temperature calcination process. In addition, the electric field treatment has the advantages of being fast and having controllable parameters. Compared with high-temperature calcination, the influence of high-temperature treatment on the conductive ion composition and the effective three-dimensional network structure is greatly reduced, the conductivity of the sodium ion conductor is greatly improved, and the production cost is greatly saved, ensuring the safety of the workshop.

[0039] 2. By providing high-priced transition metal salts and tetraethyl orthosilicate, the free diffusion of sodium ions is guaranteed to the greatest extent, thereby improving the conductivity.

[0040] In the present invention, in order to make the prepared sodium ion conductor have a stable framework structure in the crystal state, it is necessary to provide a chemical bond structure with strong covalent bond properties. Therefore, the inventors consider forming silicon-oxygen bonds so that sodium ions can diffuse freely in the channels formed by silicon-oxygen bonds. At the same time, the bottleneck sizes of silicon-oxygen bonds formed by different metal salts and different silicon-containing compounds relative to sodium ions are different, and the effects of reducing the impedance of the electrolyte body are also different. In order to effectively promote the migration of sodium ions in the crystal structure, balance the number of mobile sodium ions and the number of sodium vacancies in the electrolyte material, and inhibit the growth of dendrites inside the crystal phase, the inventors compared the effects of metal salts with different metal valences and tetraethyl orthosilicate on the prepared sodium ion conductor, and found that when a high-valence metal salt (such as a pentavalent or tetravalent metal salt) is selected, the sodium ion conductor prepared together with tetraethyl orthosilicate has better conductivity. It is analyzed that the high-valence metal ions are more likely to form a stable polyhedral three-dimensional space structure with silicon-oxygen bonds.

[0041] 3. By providing low-priced heterovalent metal salts, the excellent effect of high-priced transition metal salts on the conductive properties of sodium ion conductors can be synergistically improved.

[0042] In the process of selecting high-valent metal salts, for divalent metal salts and trivalent metal salts with poor effects, the inventors tried to further use divalent metal salts or trivalent metal salts as heterovalent metal salts on the basis of adding high-valent metal salts, in order to observe the synergistic effect between them and high-valent metal salts as transition metal salts. It has been verified that compared with not adding divalent metal salts or trivalent metal salts, the conductivity of the sodium ion conductor prepared by adding divalent metal salts or trivalent metal salts and tetraethyl orthosilicate is better. The reason may be that although single-valent metal salts can construct stable structural channels, the widely existing grain boundaries in the structural channels will also hinder the diffusion of ions, and there may be bond coupling between metals of different valences to achieve the effect of regulating grain boundaries and reducing the impedance brought by the lattice.

[0043] 4. Provides an optimal sodium salt mixing ratio; The selection of the sodium salt ratio is crucial: if the sodium salt molar ratio is too high, the bonding energy between the transition metal and the silicon-oxygen bond will be increased, which will directly affect the conductive properties of the product; if the sodium salt molar ratio is too low, the diffusion ion concentration will be low, which is not conducive to improving the conductive properties. The present invention determines the optimal sodium salt molar ratio through single factor experimental analysis. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Examples 1-8

[0046] This embodiment provides a method for preparing a solid electrolyte sodium ion conductor, comprising the following steps:

[0047] Step S1: adding a predetermined amount of sodium source, transition metal salt, isovalent metal salt, phosphorus source, and tetraethyl orthosilicate into deionized water at once, and stirring well to obtain a gel solution;

[0048] Step S2: drying the gel solution obtained in step S1, and then subjecting it to heat treatment to obtain a precursor powder;

[0049] Step S3: molding the precursor powder to obtain a green body;

[0050] Step S4: flash-sintering the obtained green body under an alternating current electric field;

[0051] Step S5: maintaining the flash-sintered green body at a preset current density for a certain period of time, then removing the AC electric field and cooling the green body to room temperature to obtain a solid electrolyte sodium ion conductor.

[0052] In the above embodiments, the selection and respective proportions of the sodium source, transition metal salt, isovalent metal salt, phosphorus source, and tetraethyl orthosilicate, as well as the process parameters in each embodiment are shown in Table 1 and Table 2:

[0053] Table 1: Raw material selection for sodium ion conductor preparation process

[0054]

[0055]

[0056] Table 2: Parameter settings for the preparation process of sodium ion conductors

[0057]

[0058]

[0059] Note: In Table 1, the molar mass of the transition metal salt is taken as 2 to convert the molar mass of each of the other components. The molar mass of the phosphoric acid aqueous solution refers to the molar mass of the phosphoric acid contained therein.

[0060] Comparative Example 1:

[0061] The difference from Example 1 is that no ethyl orthosilicate is added, and the remaining processes, materials and proportions are the same as those in Example 1.

[0062] Comparative Example 2:

[0063] The difference from Example 1 is that no transition metal salt is added, and the remaining processes, materials and proportions are the same as those in Example 1.

[0064] Comparative Example 3:

[0065] The difference from Example 1 is that no isovalent metal salt is added, and the remaining processes, materials and proportions are the same as those in Example 1.

[0066] Comparative Example 4:

[0067] The difference from Example 1 is that the molar mass of the sodium source relative to the transition metal salt is 0.5, and the other processes, materials and proportions are the same as those in Example 1.

[0068] Comparative Example 5:

[0069] The difference from Example 1 is that the molar mass of the sodium source relative to the transition metal salt is 3, and the other processes, materials and proportions are the same as those in Example 1.

[0070] Comparative Example 6:

[0071] The difference from Example 1 is that after the green body is obtained in step S3, the green body is calcined at a high temperature of 800-1000 degrees Celsius for 12 hours to obtain a solid electrolyte sodium ion conductor.

[0072] For the sodium ion conductors prepared in the above embodiments and comparative examples, the impedance of the electrolyte was tested by electrochemical impedance spectroscopy (EIS). The obtained impedance was fitted and calculated to obtain the conductivity of each electrolyte at 25 degrees Celsius, 80 degrees Celsius and 150 degrees Celsius, as shown in Table 3.

[0073] Table 3: Conductivity

[0074]

[0075] Making the battery cell:

[0076] A stainless steel foil was used as a positive electrode collector, and a vanadium pentoxide film was sputtered thereon to obtain a positive electrode. A 0.1 mm magnesium plate was used as a negative electrode. About 0.05 g of electrolyte was pressed between the positive and negative electrodes. The conductor contained 40% by mass of the conductor obtained in the above embodiment, 50% by mass of sodium hexafluorophosphate and 10% by mass of polytetrafluoroethylene to form a simple battery cell. Charge and discharge experiments were carried out at 0.1C and 4C conditions, respectively, to test the rate performance (rate performance = discharge capacity at 4C conditions / discharge capacity at 0.1C) and cycle capacity retention rate. The results are shown in Table 4 below.

[0077] Table 4: Rate performance and cycle capacity retention

[0078] Rate performance (%) Capacity retention rate after 50 cycles (%) Example 1 99.4 99.6 Example 2 98.2 99.2 Example 3 96.2 95.6 Example 4 95.1 95.3 Example 5 92.1 93.4 Example 6 93.4 93.2 Example 7 91.5 92.1 Example 8 90.3 91.9 Comparative Example 1 85.6 79.8 Comparative Example 2 85.4 77.6 Comparative Example 3 88.6 82.4 Comparative Example 4 83.4 76.4 Comparative Example 5 82.1 75.3 Comparative Example 6 78.9 70.6

[0079] Combining the data of comparative examples 1-8 and comparative examples 1-6, it can be clearly seen that the present invention, through the synergistic effect of tetraethyl orthosilicate, transition metal salt and isovalent metal salt, by adjusting the sodium ion molar ratio, further combining electric field treatment to replace the calcination process, makes the final prepared sodium ion conductor have a qualitative improvement in conductivity. Compared with the existing technology, the electrical conductivity can be increased by up to 6 orders of magnitude, and a higher electrical conductivity can be achieved at room temperature. In addition, the electrical conductivity of each embodiment is positively correlated with the rate performance and capacity retention rate of the corresponding simple battery cell.

[0080] By comparing the results of Example 1 with Comparative Examples 1 and 2, it can be seen that when neither ethyl orthosilicate nor transition metal salt is added, the conductivity will be greatly reduced, which proves that the theoretical correctness of the sodium ion conductivity is ensured by forming silicon-oxygen bonds between the two to provide a sodium ion diffusion channel;

[0081] Combined with the results of Comparative Examples 1-3, it can be seen that when tetraethyl orthosilicate and transition metal salt are added, the conductivity of the sodium ion conductor can be significantly improved; further, combined with the results of Example 1 and Comparative Example 3, it can be seen that the addition of isovalent metal salt can synergistically improve the contribution of tetraethyl orthosilicate and transition metal salt to the conductivity of the sodium ion conductor;

[0082] The results of Example 1, Comparative Examples 4 and 5 can prove that the sodium ion addition molar ratio explored by the present invention is in a relatively suitable range. Outside the range of the molar ratio of the sodium source, the transition metal salt, the isovalent metal salt, the phosphorus source and the tetraethyl orthosilicate: (1-2):2:(1.5-2.5):(0.5-1):2, a high or low sodium ion content will lead to a decrease in conductive properties.

[0083] Combining the results of Example 1 and Comparative Example 6, it can be seen that replacing high-temperature calcination with electric field treatment can significantly reduce the loss of conductivity.

[0084] The conductivity of Examples 1-4 is further improved by an order of magnitude compared with Examples 5-8. The reason may be the different selection of sodium sources: Examples 1-4 select sodium halide as the sodium source. It is speculated that sodium halide will not introduce hydrogen ions compared with sodium bicarbonate or sodium hydroxide, and hydrogen ions may have an adverse effect on the bonding energy of silicon-oxygen bonds; this phenomenon may be a future in-depth research direction for the inventor.

[0085] In Examples 1-4, the conductivity of Example 1-2 is higher than that of Example 3-4; similarly, in Examples 5-8, the conductivity of Example 5-6 is higher than that of Example 7-8; the commonality behind the difference in these two sets of values ​​is that in Examples 1-2 and 5-6, the transition metal salts are all selected from pentavalent metal salts, and the heterovalent metal salts are all selected from divalent metal salts; while in Examples 3-4 and 7-8, the transition metal salts are all selected from tetravalent metal salts, and the heterovalent metal salts are all selected from trivalent metal salts; this shows that the greater the difference in metal valence between the heterovalent metal salt and the transition metal salt, the more obvious the synergistic promoting effect of the heterovalent metal salt on the bonding between the transition metal salt and tetraethyl orthosilicate.

[0086] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sodium ion conductor, characterized in that: It is obtained by molding from a sodium source, a transition metal salt, an isovalent metal salt, a phosphorus source and tetraethyl orthosilicate through a solution-assisted solid phase reaction method; Wherein, the sodium source is selected from sodium halide, sodium bicarbonate or sodium hydroxide, and the sodium halide is selected from any one of sodium chloride or sodium fluoride; The transition metal salt is selected from pentavalent or tetravalent transition metal salts; The heterovalent metal salt is selected from divalent or trivalent heterovalent metal salts; The phosphorus source is selected from aqueous phosphoric acid.

2. The sodium ion conductor according to claim 1, characterized in that: The transition metal in the pentavalent transition metal salt is selected from any one of niobium, tantalum, antimony and arsenic; The transition metal in the tetravalent transition metal salt is selected from any one of zirconium, hafnium, cerium and tin; The transition metal salt is selected from acetate or nitrate.

3. The sodium ion conductor according to claim 1, characterized in that: The transition metal in the trivalent transition metal salt is selected from any one of iron, aluminum and chromium; The transition metal in the divalent transition metal salt is selected from any one of zinc, manganese and nickel; The transition metal salt is selected from acetate or nitrate.

4. The sodium ion conductor according to claim 1, characterized in that: The molar ratios of the sodium source, transition metal salt, isovalent metal salt, phosphorus source and tetraethyl orthosilicate are as follows: (1-2):2:(1.5-2.5):(0.5-1):

2.

5. The sodium ion conductor according to claim 1, characterized in that: The steps of molding a sodium ion conductor from a sodium source, a transition metal salt, an isovalent metal salt, a phosphorus source and tetraethyl orthosilicate by a solution-assisted solid phase reaction method are as follows: Step S1: adding a predetermined amount of sodium source, transition metal salt, isovalent metal salt, phosphorus source, and tetraethyl orthosilicate into deionized water at once, and stirring well to obtain a gel solution; Step S2: drying the gel solution obtained in step S1, and then subjecting it to heat treatment to obtain a precursor powder; Step S3: molding the precursor powder to obtain a green body.

6. The sodium ion conductor according to claim 5, characterized in that: In step S1, the amount of deionized water added is more than 20 times the mass of the sodium source; In step S2, the drying temperature is 70-80 degrees Celsius.

7. The sodium ion conductor according to claim 6, characterized in that The following steps are also included: Step S4: flash-sintering the obtained green body under an alternating current electric field; Step S5: maintaining the flash-sintered green body at a preset current density for a certain period of time, then removing the AC electric field and cooling the green body to room temperature to obtain a solid electrolyte sodium ion conductor.

8. The sodium ion conductor according to claim 7, characterized in that: In step S4, the electric field strength of the AC electric field during flash burning is 60-100 V / cm; In step S5, the holding time after flash burning is 1-10 minutes, and the preset current density is 50-70 mA / mm 2 .

9. A sodium ion solid battery, characterized in that: The invention comprises a positive electrode active material layer, a negative electrode active material layer and a solid electrolyte layer arranged between the positive electrode active material layer and the negative electrode active material layer, wherein the solid electrolyte layer contains the sodium ion conductor according to any one of claims 1 to 8.

10. The sodium ion solid battery according to claim 9, characterized in that: The mass ratio of the sodium ion conductor to the solid electrolyte layer is 20-40%.

Citation Information

Patent Citations

  • Nasicon type sodium-ion solid electrolyte, preparation method and application thereof

    CN109786815A

  • Sodium ion conductor solid electrolyte material, preparation method and application

    CN111261935A